Silver-based plasmonic nanoparticles for biosensor organophosphate pesticides using a single film containing acetylcholinesterase/choline oxidase - D. Hermanto; N. Ismillayli; H. Muliasari; R. Wirawan; S.R. Kamali (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: To address the potential harm caused by the intensive use of pesticides in pest control in agriculture, there is a need for accurate and efficient methods to detect and monitor pesticide residues. Therefore, this study aimed to develop a biosensor that can detect organophosphate pesticides highly toxic to humans and the environment. METHODS: Biosensor organophosphate pesticides using a single film containing acetylcholinesterase/choline oxidase have been designed using silver-based plasmonic nanoparticles as a colorimetric indicator. In the presence of acetylcholinesterase, acetylcholine is hydrolyzed to choline and acetic acid, then choline oxidase catalyzes the oxidation of choline to hydrogen peroxide and betaine. Hydrogen peroxide reacts with the silver nanoparticles, and the discoloration of the brown solution occurs due to the oxidation of silver+.FINDINGS: As a biosensor indicator, silver nanoparticles were extremely accurate, sensitive, and stable over a long period of storage. Transmission Electron Microscope images confirmed the reduction in size of nanoparticles from 16.82 ± 4.36 to 9.63 ± 2.29 nanometers. The analyte profenofos, one of the organophosphate pesticides, inhibits the activity of acetylcholinesterase, thereby reducing the concentration decrease of silver nanoparticles by releasing less hydrogen peroxide. Optimum conditions for biosensors were achieved with a potential of Hydrogen of 7, buffer, and acetylcholinesterase concentrations of 7 and 70 millimolar, respectively, with an incubation time of 5 minutes. Biosensor response showed a linear range at profenofos concentrations of 0.05-2.00 milligrams per liter, with limits of detection and quantization of 0.04 and 0.13 milligrams/liter, respectively. Biosensor also has excellent sensitivity, reproducibility, and stability, with a Relative Standard Deviation of 2.5 percent and a stable response of up to 4 months. Subsequently, using a biosensor in the chilli as a sample resulted in a profonefos level of 0.04 milligrams per liter, making it safe for consumption.   CONCLUSION: Biosensor measurement outcome aligned with the gas chromatography-mass spectrometry result, which is the accepted standard method for detecting profenofos. Additionally, the proposed biosensor offers several advantages such as ease of use, fast, low-cost, and on-site analysis. Hence, this method is suitable for monitoring and controlling pesticide residues, particularly organophosphate, in agricultural products and the environment.